The Transformation of Ḥifẓ Al-'Ird in Contemporary Uṣūl Al-Fiqh: A Maqāṣid Framework for The Protection of Digital Dignity in The Deepfake Era - Nursobah, Achmad (Kartika: Jurnal Studi Keislaman, 2026)
This article departs from a new anxiety in the world of Islamic law: human dignity is now threatened not only in the social-physical space, but also in the digital space. The deepfake phenomenon has given birth to a form of slander that is so convincing that it can damage reputations, collapse public trust, and even cause economic losses. With a doctrinal qualitative approach enriched by the AIRE (authenticity, integrity, reliability, explainability) digital forensic standard, this study reconstructs the concept of ḥifẓ al-ʿirḍ in uṣūl al-fiqh to be relevant to contemporary digital challenges. The results of the study map the typology of digital slander: sexualization, political manipulation, and financial fraud and classify digital evidence into three levels: valid as bayyinah, just forensic qarīnah, or must be rejected. The analysis of maqāṣid shows that the protection of dignity can defeat the claim of freedom of expression when the negative impact is greater. From this was born new ideas: al-bayyinah al-raqmiyyah as a standard of digital evidence, karāmah al-raqmiyyah, which equates digital insults with qadhf, and the selective application of the principle of sadd/fatḥ al-żarāʾiʿ to AI technology. This article then offers a maqāṣid framework for the protection of digital dignity with four layers: prevention, detection, adjudication, and remediation as a bridge between classical legal theory and modern forensic practice, while presenting a blueprint for the protection of dignity in the digital age